Two‐Dimensional (2D) or Quasi‐2D Superstructures from DNA‐Coated Colloidal Particles. Issue 11 (1st February 2021) - Liu, Mingzhu; Zheng, Xiaolong; Grebe, Veronica; He, Mingxin; Pine, David J.; Weck, Marcus
Abstract: This contribution describes the synthesis of colloidal di‐patch particles functionalized with DNA on the patches and their assembly into colloidal superstructures via cooperative depletion and DNA‐mediated interactions. The assembly into flower‐like Kagome, brick‐wall like monolayer, orthogonal packed single or double layers, wrinkled monolayer, and colloidal honeycomb superstructures can be controlled by tuning the particles' patch sizes and assembly conditions. Based on these experimental results, we generate an empirical phase diagram. The principles revealed by the phase diagram provide guidance in the design of two‐dimensional (2D) materials with desired superstructures. Our strategy might be translatable to the assembly of three‐dimensional (3D) colloidal structures. Abstract : Colloidal 2D superstructures such as orthogonal packed single or double layers, flower‐like Kagome, honeycomb structures, brick‐wall like monolayer, and wrinkled monolayer can be assembled from DNA‐coated di‐patch particles in a bottom‐up fashion.